Comparative Study of Rumen Ciliate Fauna of Goat and Sheep in Libya - Gözde Gürelli; Asem Ramadan Amar Mohamed (Türkiye Parazitoloji Dergisi, 2021)

(untitled)
Objective:This study aims to provide comparative information on the rumen ciliate fauna of goat (Capra aegagrus hircus) and sheep (Ovis aries) living in Zawiya, Libya.Methods:We obtained rumen samples from 16 goats and 17 sheep after the slaughter in Zawiya, Libya between June and August 2016. We immediately fixed the well-mixed samples with an equal volume of 18.5% formalin. We filtered and stained the samples in the laboratory with methyl green formalin saline solution to determine the nuclei and added 2% Lugol’s iodine solution to visualize the skeletal plates.Results:We found that the mean number (± standard deviation) of ciliates in the rumen contents from goats and sheep was 70.9±61.6×104 cells mL-1 (minimum-maximum value, 4.0-187.0×104 cells mL-1) and 96.3±49.3×104 cells mL-1 (minimum-maximum value, 19.5-235.0×104 cells mL-1), respectively. Results also showed that the total number of species per goat and sheep was 1-17 (mean, 8.2±4.7) and 1-13 (mean, 7.9±3.8), respectively. We identified 10 genera, 19 species, and 11 morphotypes in goats and 9 genera, 16 species, and 13 morphotypes in sheep. Additionally, we found that Entodinium simulans prevalence in all goats and sheep was 100%. On the other hand, we observed Hsiungia triciliata and Ostracodinium gracile in only one goat (6.3% prevalence) and Polyplastron multivesiculatum in only one sheep (5.9% prevalence). Overall, the ruminal ciliate fauna of goat and sheep in Libya comprised Entodinium species (mean for goats, 85.9%; mean for sheep, 83.5%).Conclusion:This study recorded Hsiungia triciliata as a new endosymbiont in goats. To our knowledge, this study is the first to report all of the species detected in goats from Libya. Similarly, this is the first to detect Diplodinium anisacanthum, Entodinium bursa, E. ellipsoideum, E. longinucleatum, E. simulans, Isotricha prostoma, Ophryoscolex caudatus, Ostracodinium gracile, and Polyplastron multivesiculatum in sheep from Libya.